SENGKETA HAK GARAP DAN PENGUASAAN TANAH DI KALICARI SEMARANG (Studi Putusan Mahkamah Agung Nomor 153 PK/TUN/2013) - Mega Dewanti, Pinanti; Sukirno, Sukirno (Magister Kenotariatan Universitas Diponegoro, 2019)
A dispute between the Plaintiff and the Government of Semarang City on the issuance of the Decree of Mayor of Semarang, Number: 143/285/2002 on Determination of Land of Former Bengkok and Building of Asset of Kelurahan Being Semarang City Government's Asset. The problems that arise in this writing is how the legitimacy of the release of land rights and compensation claim based on the Supreme Court Decision Number 153 PK / TUN / 2013 whether has provided legal certainty for the owner. The conclusion of this legal writing, that the Panel of Judges is negligent in observing the validity of arable land in deciding cases that give the decision of the cancellation of the Decree of Mayor of Semarang Number 143/285/2002 dated September 12, 2002, concerning Determination of Land of Bengkok and Building of Asset of Village to Government's Asset Semarang City because Ny. Murdyaningsih has not been able to prove the origin of the land that became the case according to the prevailing laws and regulations. Keywords: Land Dispute, Right to Develop Land and Mastery Land. Abstrak Sengketa antara Penggugat dengan Pemerintah Kota Semarang atas di terbitkannya Surat Keputusan Walikota Semarang, Nomor: 143/285/2002 tentang Penetapan Tanah Bekas Bengkok dan Bangunan Aset Kelurahan Menjadi Aset Pemerintah Kota Semarang. Permasalahan yang timbul dalam penulisan ini adalah bagaimana keabsahan pelepasan hak dan ganti kerugian tanah garapan berdasarkan Putusan Mahkamah Agung Nomor 153 PK/TUN/2013 apakah telah memberikan kepastian hukum bagi pemiliknya. Kesimpulan dari penulisan hukum ini, bahwa Majelis Hakim lalai dalam mencermati mengenai keabsahan tanah garapan dalam memutus perkara yang memberi putusan pembatalan Surat Keputusan Walikota Semarang Nomor 143/285/2002 tanggal 12 September 2002, tentang Penetapan Tanah Bekas Bengkok dan Bangunan Aset Kelurahan Menjadi Aset Pemerintah Kota Semarang karena Ny. Murdyaningsih belum dapat membuktikan asal-usul tanah yang menjadi perkara sesuai ketentuan peraturan perundang-undangan yang berlaku. Kata Kunci: Sengketa Tanah, Hak Garap dan Penguasaan.